Identification of a PTEN mutation with reduced protein stability, phosphatase activity, and nuclear localization in Hong Kong patients with autistic features, neurodevelopmental delays, and macrocephaly. Issue 8 (2nd April 2018) - Wong, Chi Wai; Or, Penelope Mei Yu; Wang, Yubing; Li, Lisha; Li, Jing; Yan, Mingfei; Cao, Ye; Luk, Ho Ming; Tong, Tony Ming For; Leslie, Nick R.; Lo, Ivan Fai‐Man; Choy, Kwong Wai; et al.
Abstract : PTEN is a tumor suppressor gene inactivated in over 30% of human cancers. It encodes a lipid phosphatase that serves as a gatekeeper of the phosphoinositide 3‐kinase signaling pathway. Germline mutation frequently occurs in this gene in patients diagnosed with PTEN Hamartoma Tumor Syndrome (PHTS). PHTS individuals are characterized by macrocephaly, benign growth of multiple tissues and increased tumor risk. In addition, autistic phenotypes are found in 10–20% of individuals carrying the germline PTEN mutation with macrocephaly. In this report, 13 suspected PHTS patients were screened for mutation in the PTEN gene. A missense variant (c. 302T > C) substituting the isoleucine at codon 101 to a threonine, a single nucleotide insertion (c. 327‐328insC) causing a frame shift mutation and termination at codon 109, and a nonsense variant (c. 1003C > T) truncated the protein at codon 335 were identified. The I101T mutation significantly reduced PTEN protein expression levels by 2.5‐ to 4.0‐fold. Mechanistically, I101T reduced the protein half‐life of PTEN possibly due to enhanced polyubiquitination at Lysine 13. However, the I101T mutant retained almost 30% of the lipid phosphatase activity of the wild‐type protein. Finally, the I101T mutant has reduced phosphorylation at a PTEN auto‐dephosphorylation site at Threonine 366 and a lowered ratio of nuclear to cytosolic protein level. These partial losses of multiple PTEN biochemical functions may contribute to the tissue overgrowth and autistic features of this PHTS patient. Autism Res 2018, 11: 1098–1109 . © 2018 The Authors Autism Research published by International Society for Autism Research and Wiley Periodicals, Inc. Lay Summary: The genetics of autism spectrum disorders is highly complex with individual risk influenced by both genetic and environmental factors. Mutation in the human PTEN gene confers a high risk of developing autistic behavior. This report revealed that PTEN mutations occurred in 23% of a selected group of Hong Kong patients harboring autistic features with gross overgrowth symptoms. Detailed characterization of a PTEN mutation revealed reduced protein stability as one of the underlying mechanisms responsible for reduced PTEN activity.